PERAN PEMERINTAH DESA DALAM PENGELOLAAN DAYA TARIK WISATA DI DESA KARANG BAJO, KECAMATAN BAYAN, KABUPATEN LOMBOK UTARA - Herfan Sabandi; Lalu Masyhudi; Lalu Mohamad Iswadi Athar (Journal Of Responsible Tourism, 2023)
This study discusses the role of the Karang Bajo Village Government as a Tourist Attraction in North Lombok Regency. This research was conducted to answer the problems in question, namely to determine the role of government in managing tourist attractions. This writing is presented descriptively to obtain an overview of the role of government and the management of tourist attractions. The method used in collecting data is by observation, interviews, documentation and literature study. The results of this study indicate that the role of the village government in managing tourist attractions is very important in terms of the government's ability to organize Karang Bajo Village. The role of the government as a stakeholder is very visible both as a policy creator, coordinator, facilitator, implementer, and as an accelerator. The conclusion that can be drawn regarding the role of the village government in the management of tourist attractions is that the important role of stakeholders in the management of tourist attractions in Karang Bajo Village is very much needed in order to maintain and preserve the culture in Karang Bajo Village. Karang Bajo Village still has room to develop and compete in the tourism world of North Lombok Regency.